Smart Meter Modelling and Fault Location Communication in Smart Grid - Velhal Vilas; V. Muralidhara; Shashikant Bakre; Vaishali Velhal (Majlesi Journal of Electrical Engineering)
This paper includes a novice technique for locating single line to ground fault in electrical transmission network.  Validation of the proposed algorithm is demonstrated using matlab simulink. Simpower system tool box is used for the modeling of smart meter, transmission lines and single line to ground fault (1L-G). A novel method is proposed to countercheck whether the fault has occurred really or not. Data related to 1l-G fault has been collected at 220kV Lonikand substation and analyzed. c exclusively during the visit at Kalkitech (top manufacturing company of Intelligent Electronic Devices (IEDs) in Bangalore, Karnataka, India). Effect of harmonics on fault current measurement using smart meter is elaborated. Advancements in communication technology are illustrated from asset management perspective.